EVALUASI KOMPETENSI DAN DAMPAK PELATIHAN GREEN SHIPPING PADA AWAK KAPAL - Samekto, Agus Aji (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2025)
The global maritime industry's transition towards sustainable operations, or green shipping, is driven by increasingly stringent international regulations and heightened environmental awareness. However, the success of this transition critically depends on the readiness and competence of its frontline human resources: the ship's crew. This research aims to evaluate the implementation of a specialized green shipping training program for seafarers, focusing on competency needs analysis and the measurement of its impact on operational performance. Utilizing a mixed-methods research design anchored in the Kirkpatrick Model of Evaluation, this study integrates quantitative data from pre- and post-training assessments and operational Key Performance Indicators (KPIs) with qualitative data from surveys and in-depth interviews. The findings indicate that the structured training significantly enhanced crew knowledge of energy efficiency regulations (EEXI and CII), technical skills in operating energy-saving technologies such as trim optimization software, and the application of more efficient operational behaviors on the job. Quantitatively, the training implementation demonstrated a measurable positive impact on operational performance, including a reduction in average fuel consumption, improved transit time efficiency, and lower operational costs per nautical mile. This study provides robust empirical evidence that investment in human capital through training is a crucial and strategic element for achieving regulatory compliance, competitive advantage, and decarbonization goals in the shipping industry.